Recent physical connections may explain weak genetic structure in western Alaskan chum salmon (Oncorhynchus keta) populations. Issue 7 (13th June 2013) - Garvin, Michael R.; Kondzela, Christine M.; Martin, Patrick C.; Finney, Bruce; Guyon, Jeffrey; Templin, William D.; DeCovich, Nick; Gilk‐Baumer, Sara; Gharrett, Anthony J.
Abstract Low genetic divergence at neutral loci among populations is often the result of high levels of contemporary gene flow. Western Alaskan summer‐run chum salmon (Oncorhynchus keta) populations demonstrate weak genetic structure, but invoking contemporary gene flow as the basis for the low divergence is problematic because salmon home to their natal streams and some of the populations are thousands of kilometers apart. We used genotypes from microsatellite and single nucleotide polymorphism loci to investigate alternative explanations for the current genetic structure of chum salmon populations from western Alaska. We also estimated current levels of gene flow among Kuskokwim River populations. Our results suggest that weak genetic structure is best explained by physical connections that occurred after the Holocene Thermal Maximum among the Yukon, Kuskokwim, and Nushagak drainages that allowed gene flow to occur among now distant populations.